189k views
5 votes
Write the expression without a negative exponent.1/a^-4

User Apilat
by
6.1k points

1 Answer

2 votes

Explanation

We are given the expression below:


(1)/(a^(-4))

We are required to rewrite the expression without a negative exponent.

This can be achieved thus:


\begin{gathered} (1)/(a^(-4)) \\ We\text{ }know\text{ }from\text{ }indices\text{ }that\text{ }a^(-x)=(1)/(a^x) \\ \therefore(1)/(a^(-4))=1/ a^(-4)=1/(1)/(a^4) \\ =1*(a^4)/(1)=a^4 \end{gathered}

Hence, the answer is a⁴.

User Startuprob
by
6.0k points